Presidential Popularity and Macroeconomic Performance: Are Voters Really so Naive? - Chappell, Henry W. (The Review of Economics and Statistics, 1983)
The article focuses on the relationships between the macroeconomic performance of political administration and their popularity or vote getting ability. All of the studies that has been performed to analyze the relationships agree that votes and popularity can be explained well by models which suppose that voters judge policy makers on the basis of retrospective evaluation of past macroeconomic outcomes. While conventional popularity functions assume that voters simply punish inflation and reward output or low unemployment, voters who understand the long and short run relationships noted above would evaluate policymakers differently. Inflation in a given period is largely determined by past expectations of inflation, which cannot easily be controlled by current policy choices. The results of a study done by the author, show that data on presidential popularity are consistent with the hypothesis that voters are concerned with the future consequences of current economic policy choices and are aware of the nature of constraints imposed by economic reality.